2000
DOI: 10.1046/j.1360-0443.2000.95460111.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Minnesota Model approach in the treatment of adolescent drug abusers

Abstract: Favorable treatment outcome for drug abuse was about two to three times more likely if treatment was completed. Also, there were no outcome differences between residential and outpatient groups. Alcohol was the most common drug used during the follow-up period, despite cannabis being the preferred drug at intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 0 publications
8
97
0
5
Order By: Relevance
“…The pattern of outcome data associated with the treatment group is comparable to outcome findings observed in other adolescent drug treatment studies, including those that have investigated general 12-Step approaches (Harrison & Hoffman, 1989;Winters et al, 2000) and other treatment approaches (Deas & Thomas, 2001;Williams et al, 2000). However, when the separate treatment groups defined by typology are examined, a different outcome picture emerges.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The pattern of outcome data associated with the treatment group is comparable to outcome findings observed in other adolescent drug treatment studies, including those that have investigated general 12-Step approaches (Harrison & Hoffman, 1989;Winters et al, 2000) and other treatment approaches (Deas & Thomas, 2001;Williams et al, 2000). However, when the separate treatment groups defined by typology are examined, a different outcome picture emerges.…”
Section: Discussionsupporting
confidence: 51%
“…This study extends our prior work that described short-and long-term outcome among adolescents with a substance dependence disorder and who received 12-Step treatment (Winters, Stinchfield, Opland, Weller, & Latimer, 2000;Winters, Stinchfield, Latimer, & Lee, 2007). The present analysis will extend our outcome descriptive studies by examining the relationship between internalizing and externalizing symptoms among this group of substancedependent adolescents.…”
Section: Introductionsupporting
confidence: 62%
“…As was already reported in other documents, any drinking does not necessarily imply a progress in relapse considering more complex treatment outcomes (Stout, 2000;Winters, Stinchfield, Opland, Weller, & Latimer, 2000), even with more addictive substances such as heroin (Gossop, Stewart, Browne, & Marsden, 2002). In the same vein, results obtained with the definition of any drinking are not associated with changes in post-treatment drinking patterns (Bennett et al, 2005;Maisto et al, 2003).…”
Section: Discussionsupporting
confidence: 68%
“…For example, Tait et al 30 reported a mean age of 16.7 years (SD: 1.8 years) and an age range of 12 to 19 years in a study of the effectiveness of emergency department AOD abuse intervention among 127 adolescents, with 86% of the participants being Ն15 years of age. Similarly, Winters et al 8 reported an age range of 12 to 18 years in a study of the effec-tiveness of Minnesota Model treatment among 179 adolescents, with 60% of the participants being Ն16 years of age. Therefore, it seems that findings from many, if not most, published studies of adolescent alcohol abuse treatment are derived primarily from the oldest of the National Institute on Alcohol Abuse and Alcoholism Underage Drinking Initiative groups, namely, youths 16 to 20 years of age.…”
Section: Age and Grade As Proxies For Developmental Levelmentioning
confidence: 99%
“…8,30,34,[38][39][40][41][42] Although each of these indicators has considerable face validity and is likely to be correlated significantly and positively with the other indicators, the extent to which each of these indicators is a developmentally appropriate representation of adolescent alcohol use problems remains unknown. With the exception of scales measuring negative consequences of drinking, which tend to emphasize developmentally relevant events such as "trouble at school" or "made excuses to your parents about your alcohol use," the conventional outcomes used in alcohol treatment research with adolescents are derived directly from those used in alcohol treatment research with adults.…”
Section: Developmentally Appropriate Outcomesmentioning
confidence: 99%